A Fault Detection and IoT Monitoring System for Single-Phase Wiring - Chui, Jovin; binti Bohari, Azuwien Aida (Progress in Engineering Application and Technology, 2023)
Fault detection and IoT monitoring are essential tools used in single phase wiring systems to ensure the smooth operation of electrical appliances and to detect any faults or anomalies in the system. The Internet of Things (IoT) enables real-time monitoring of the system, allowing for immediate detection of any issues that may arise. With fault detection and IoT monitoring, single phase wiring systems can operate reliably, providing uninterrupted power to homes and businesses. Failure is one of the consequences of a shorted circuit, in addition to the wire system. Furthermore, some issues can cause the system to be disrupted and fail to effectively supply energy to the loads, such as physical faults, which can be internal or external and generally include cable damage and leakage. As every form of power that is delivered to the consumer has flaws and issues, such a voltage supply to the consumer may be over or less. The proposed solution has significant potential to improve the operation and maintenance by develop a power monitoring and fault detection that controlled by the microcontroller and sensor to detect the input and output of the electricity distribution networks. Furthermore, this project proposes a power monitoring and fault detection system for electricity distribution networks. This system is capable to monitor and record the electrical parameter such as voltage and current consumption of the system. This project successfully developed a reliable fault detection and IoT monitoring system for single-phase wiring systems and send notifications to the user via Blynk application.